IT governance implementation in public agency towards transformational government readiness / Ainihilya Saipol Bahri - Saipol Bahri, Ainihilya (2014)
The emergence of transformational government from enhancement of e government and improve e-government failure. Within the emergence, this research motivates to define transformational government in Malaysia perspective. IT governance stated as critical enabler transformational government. The shared vision for future outcome and cross-collaboration is required in transformational government. In order to have those, important to measure IT governance which align business operation and IT potential is effective. However, the role of IT governance is not clear towards transformational government and how the IT governance contributes to transformational government. The aim of this research is to identify IT governance effectiveness in public sector towards Transformational Government readiness. The assessment on IT governance practices within public agencies. Within the scope of this research, it wants to identify the role of IT governance within the public agencies. Identification of the IT governance role is from how the organization define IT governance. Second objective is to determine IT governance's mechanism implementation in public sector using IT governance practices items. Third objective is to investigate practices of the public agencies to align between business and IT from corporate structure, IT function and IT governance practices. This research using qualitative approach and done on case study at EPU, ICU, MOF and MAMPU. The result shows that each public agency define IT governance role to collaborate between IT and business and also role of IT to enable collaboration between business units and IT. All the public agencies practices IT governance in structure, process and relational mechanism. Furthermore, the public agencies align between IT and business using different approach based on the organization environment.